PEMENUHAN KEBUTUHAN AIR BERSIH DI KELURAHAN KAPUK MUARA OLEH PEMDA DKI JAKARTA - Devika Anindya Sari; Sri Untari Indah Artati (Reformasi Hukum Trisakti, 2022)
The state hereby participates in ensuring the people's right to water, which is also referred to as the people's right to water in the process. The issue at hand is whether the provision of clean water in RW 01 Kapuk Muara Village complies with Law Number 17 of 2019 regarding Water Resources, and how the local government manages the provision of clean water to residents of RW 01 Kapuk Muara Village. Normative legal research was conducted to address the issue, and the nature of the research was descriptive and the data used were secondary and primary data and the data were analyzed qualitatively, drawing conclusions using deductive logic. The results of the study stated that the fulfillment of clean water in the RW 01 area of ​​Kapuk Muara Village was not in accordance with the Law on Water Resources. Apart from that, the fulfillment of clean water by the DKI Jakarta regional government also has problems, namely in the Jakarta area raw water is very small in quantity and also in poor quality and in Jakarta itself there is no special reservoir that functions as a raw water reservoir.